Induksi Tunas in vitro Jeruk Siam (Citrus nobilis Lour.) Asal Kampar pada Berbagai Konsentrasi Sukrosa - FATONAH, SITI; ISDA, MAYTA NOVALIZA; LESTARI, WAHYU (Jurnal Riau Biologia, 2016)
This study aimed to determine the most effective concentration of sucrose for a shoot induction fromcotyledon explants of Citrus nobilis from Kampar. Cotyledon explants were cultured on Murashige andSkoog (MS) medium containing sucrose at various concentrations without supplemented with growthregulators. The treatments consisted of five concentrations of sucrose, i.e. 0, 20, 30, 40, 50, 60 g /l. Theresult showed that all explants on different concentrations of sucrose treatment had the percentage ofliving and the percentage of shoot induction reached 100%. The best response for shoot induction aftereight weeks of culture was observed on MS medium supplemented with 50 g/l sucrose with the number ofshoot was 2, shoot length was 4,125 cm, and leaf number was 5,74 strands.Key words: Citrus nobilis lour., concentration of sucrose, in vitro, shoot induction